USE OF BOTULINUM TOXIN IN SPASTIC CEREBRAL PALSY, REVIEW OF LITERATURE - Aleksić, Marko; Baščarević, Zoran (Medicinski podmladak, 2019)
Botulinum toxin type A is a protein that is synthetized by Clostridium botulinum. It represents one of the most potent toxins in nature. It is a cause of poisoning (botulism), but it also has a beneficial effect on reducing muscle spasm and has found widespread use in medicine, with indications increasing year by year. If properly dosed, complications are rare and without major consequences. In the treatment of spastic cerebral palsy, it is beneficial in reduction of spasm. The effect is localized and systemic side effects are absent. The patient’s acceptance of this therapy is very good. The effect on the gait pattern can be maintained at a satisfactory level between 3 and 6 months after administration. The interval between therapies is about 3 months, provided that constant control of motor function of the spastic limb is ensured. Better results are achieved on passive movements than active movements. Effects are transient and reversible. Therapy should be started at an early age before the development of contractures, because deformity can be prevented. Botulinum toxin type A therapy is considered to be the pharmacological therapy of choice in the treatment of spastic deformities in patients with cerebral palsy, due to its reversible effects, low rate of side effects, painlessness, and the possibility of repeated therapy. Keywords: cerebral palsy, botulinum toxin, spastic deformity, electromyoneurography, skeletal muscle